Integrating Business Process Improvement and Information Systems to Improve Service Quality: A Conceptual Model - Pipin Anggaliya; Endang Chumaidiyah (IPTEK Journal of Proceedings Series, 2020)
PT. X is a company that is engaged in testing telecommunications equipment. In its business activities there are some special problems in the current business processes and information systems that are not optimal. This research was conducted to examine the quality of services produced by business processes and information systems used today. The method used is to integrate Business Process Improvement with information systems to improve service quality. The results obtained from this study consist of a conceptual model for getting business processes and designing information systems that have accommodated business process and service improvements.